1996
DOI: 10.1177/036354659602400503
|View full text |Cite
|
Sign up to set email alerts
|

A Muscle-Splitting Approach to the Ulnar Collateral Ligament of the Elbow

Abstract: The standard surgical approach for repair or reconstruction of the ulnar collateral ligament of the elbow involves lifting off of the tendon of the common flexor bundle at its origin on the medial epicondyle. However, a more limited muscle-splitting approach may be feasible. A muscle-splitting approach is less traumatic to the flexor-pronator muscle mass, and it could decrease operative time and lessen immediate morbidity after surgery. A proposed muscle-split through the common flexor bundle extends from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
119
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(119 citation statements)
references
References 10 publications
0
119
0
Order By: Relevance
“…The same review identified several advancements in the original technique that appear to be associated with improved rate of return to prior level of play and decreased complication rate. One of the most significant modifications is the development of the muscle splitting technique as described by Smith et al [31] The original description of this technique was accompanied by a 0 % ulnar neuropathy rate in their series of 22 patients at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The same review identified several advancements in the original technique that appear to be associated with improved rate of return to prior level of play and decreased complication rate. One of the most significant modifications is the development of the muscle splitting technique as described by Smith et al [31] The original description of this technique was accompanied by a 0 % ulnar neuropathy rate in their series of 22 patients at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A standard release is not performed routinely. A longitudinal split is made in the flexor carpi ulnaris (Smith et al 1996). The sublime tubercle at the proximal ulna and the medial epicondyle of the humerus are completely exposed.…”
Section: Reconstructionmentioning
confidence: 99%
“…The sublime tubercle of the ulna is a small protuberance on the medial aspect of the cornnoid process of the ulna onto which the anterior band of the medial collateral ligament inserts [3]. In this report we describe three throwing athletes with avulsion injuries of the sublime tubercle of the ulna whose injuries were diagnosed with a combination of MR arthrography and plain radiography.…”
mentioning
confidence: 97%
“…3-mm section with 1-mm interslice gap, and 16-cm field of view) were acquired using a 5-inch (12.7-cm) general purpose coil. Two of the patients had surgical exploration of the medial elbow joint.…”
mentioning
confidence: 99%